Impact of Chronic Spontaneous or Inducible Urticaria on Occupational Activity - Amandine Baudy; Nadia Raison-Peyron; Chris Serrand; Marie-Noëlle Crépy; Aurélie Du-Thanh (Medical Journals Sweden, 2024)
The impact of chronic urticaria on work has been scarcely reported, whereas its peak incidence is between the ages of 20 and 40. The aim of this study was to assess the occupational impact of chronic urticaria and its treatment, by combining objective and patient-reported data. A monocentric observational study was performed using questionnaires over a 1-year period from 2021 to 2022 in chronic urticaria patients who were in a period of professional activity and agreed to participate. Of the 88 patients included, 55.7% assessed the occupational impact of their chronic urticaria as significant, and even more severe when chronic urticaria was poorly controlled. Some 86% of patients had symptoms at work, in a third of cases aggravated by work. However, occupational physical factors were not associated with an aggravation of inducible chronic urticaria. A total of 20% reported treatment-related adverse effects affecting their work. Despite low absenteeism, presenteeism and reduced productivity were important (> 20%). Six patients (6.8%) had difficulties keeping their work. For 72.7% of the patients, the occupational physician was not informed. The occupational impact of chronic urticaria should be discussed during consultations, particularly when it is insufficiently controlled. The occupational physician should be informed in order to support patients' professional project.